The quantitative effect of drying on the surface color change of reaction woods: Spruce compression wood (Picea abies L.) and poplar tension wood (Populus nigra L.) - Tarmian, Asghar; Foroozan, Zeynab; Gholamiyan, Hadi; Gerard, Janin (Drying Technology, 2011)
The surface color change of compression wood in spruce (Picea abies L.) and tension wood in poplar (Populus nigra L.) due to drying was investigated using CIE LAB and CIELCh colorimetry techniques. The results showed that the compression wood was lighter, yellower, less red, and more statured in color with a deeper hue after drying. Similar changes were also seen with the tension wood, except that it was less yellow and less statured in the dry condition. The color change (ΔE) of compression wood was found to be more remarkable than that of tension wood. Overall, the difference in the colorimetric parameters between the reaction woods and their corresponding normal woods was less significant after drying. © 2011 Taylor & Francis Group, LLC.
Created from Fastlane, Scopus look-up
Keywords: Color; Drying; Reaction wood